Restorative Justice in Juvenile Criminal - Probosiwi, Ratih (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The study aims to determine the application of restorative justice in juvenile criminal after the enactment of the Child Criminal Justice System seen from the aspect of regulation, infrastructure, institutions and human resources from the investigation until the prosecution. The study was conducted in Central Java at the number of cases of violence and sexual crimes against children whether done by adults or children. The primary data obtained by structured interviews through questionnaire and enriched bydeep interviews, observation, focus group discussions and literature review. Research shows that the Central Java is alert and ready to face the change of juvenile criminal justice paradigm from retributive and restitutiveto restorative justice. Some regulations have been made to protect children, especially victims. Law enforcement agencies have also been trying to complete juvenile criminal justice through infrastructures and budgets, although still limited. In practice, limited human resources both in terms of quantity as well as the knowledge and skills of handling ABH become one of the bottlenecks. It is expected that the government is able to increase resources through recruitment and procurement implementing technical training.